Cabinda: Africa’s Forgotten War - Shantz, Jeff (UnderCurrents: Journal of Critical Environmental Studies, 2006)
With the cessation of conflict between the Angolan government and UNITA (União Nacional para a Independencia Total de Angola) militias, in April 2002, attention turned to the ongoing separatist conflict in Cabinda. An oil-rich enclave separated from the rest of Angola by a slender strip of territory of the Democratic Republic of Congo, Cabinda has been the site of a decades-long war of independence between the Angolan government and various separatist factions, a struggle that has been called “Africa’s forgotten war.” Approximately 30,000 people have lost their lives in almost 30 years of struggles for independence. Despite the severe humanitarian crisis, access to the enclave has been largely closed to all but those who work in the oil industry.